Tradition and education in The awakening of Miss Prim - Teresa Pueyo Toquero (Ignatianum University Press, 2018)
The awakening of Miss Prim is a novel that tells the story of Prudencia Prim in the small town of San Ireneo de Arnois. In the novel, Prudencia is surprised by the way of life of the irenites, who seem to despise the modern world. The novel serves as a framework for ideas that go far beyond the plot. It is a reflection on the value of truth, good and beauty and how they crystallized in Western civilization. This paper aims to shed some of the main ideas that give substance to the novel and gauge its value. In particular, the relationship between the present and the past, between tradition and progress and the option of accommodation or rebellion against current mainstream dynamics, will be valued. Finally, this paper will try to show how the whole novel revolves around the notion that there is a truth and that it is beautiful and what role that truth has in human life. Chesterton, G.K. (1912, November 13). Civilization and progress, Illustrated London News, published in Armstrong, D. (2009). The Wisdom of Mr. Chesterton: The Very Best Quotes, Quips, and Cracks from the Pen of G.K. Chesterton. Saint Benedict Press. Ecuyer l', C. (2014). The wonder approach to learning. Frontiers in human neuroscience, 8, 764. Enkvist, I. (2006). Repensar la Educación. Ediciones internacionales universitarias. John Paul II (1999). Letter to artists. Retrieved from http://w2.vatican.va/content/john-paul-ii/es/letters/1999/documents/hf_jp-ii_let_23041999_artists.html Lewis, C.S. (2013). Screwtape Letters: Annotated Edition, The. HarperOne. __. (2015). Mere Christianity. HarperOne. Pearce, J. (n.d.). Interview with Author Joseph Pearce on "Lord of the Rings", New York, Nov. 19th 2001, originally published at ZENIT.org. Retrieved from https://www.catholiceducation.org/en/culture/art/interview-with-author-joseph-pearce-on-lord-of-the-rings.html Prada de, J.M. (2016, November 14). El latín y los muertos.XL semanal.Retrieved from http://www.xlsemanal.com/firmas/20161114/latin-los-muertos.html